Advancement of Electrochemical Thermoelectric Conversion with Molecular Technology. (22nd November 2022) - Zhou, Hongyao; Inoue, Hirotaka; Ujita, Mizuha; Yamada, Teppei
Abstract: Thermocells are a thermoelectric conversion technology that utilizes the shift in an electrochemical equilibrium arising from a temperature difference. This technology has a long history; however, its low conversion efficiency impedes its practical usage. Recently, an increasing number of reports have shown drastic improvements in thermoelectric conversion efficiency, and thermocells could arguably represent an alternative to solid thermoelectric devices. In this Minireview, we regard thermocells as molecular systems consisting of successive molecular processes responding to a temperature change to achieve energy generation. Various molecular technologies have been applied to thermocells in recent years, and could stimulate diverse research fields, including supramolecular chemistry, physical chemistry, electrochemistry, and solid‐state ionics. These research approaches will also provide novel methods for achieving a sustainable society in the future. Abstract : Thermocells are a type of battery that produces electricity from a temperature difference between the two electrodes. Recent studies have shown various molecular technologies can be effectively used in thermocells to increase the voltage. This Minireview provides a thorough comparison of four basic strategies—redox entropy, molecular recognition, phase separation, and phase transition—for boosting the thermoelectric efficiency.